Radical algebras subgroups of whose adjoint groups are subalgebras - Popovich, S. V.; Sysak, Ya. P. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We obtain the characteristic for radical algebras subgroups of whose adjoint groups are subalgebras. In particular, we prove that the algebras of this sort are nilpotent with nilpotent length at most three. We give the complete classification of those algebras under consideration which are generated by two elements.